Mechanisms of Mitotic Chromosome Segregation - J. Richard McIntosh (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book describes current knowledge about the mechanisms by which cells segregate their already duplicated chromosomes in preparation for cell division. Experts in the field treat several important aspects of this subject: (1) the history of research on mitotic mechanisms, to serve as a background; (2) assembly of the mitotic spindle; (3) Kinetochore assembly and function; (4) the mechanisms of chromosome congression to the metaphase plate; (5) the spindle assembly checkpoint; (6) mechanisms to avoid and correct erroneous chromosome attachments to the spindle; (7) a molecular perspective on spindle assembly in land plants; (8) chromosome segregation in anaphase A; (9) spindle elongation in anaphase B; and (10) the consequences of errors in chromosome segregation. Each chapter provides the reader with a comprehensive and accurate picture of current research in a form that is both readable and authoritative. The volume is suitable for scholars in this and related fields and for teaching at an advanced level.